Revitalizing the Crisis Music Culture of the Moken in Surin Archipelago National Park, Pang-nga - Ungpho, Rewadee; Chandransu, Nantida (Journal of Liberal Arts Prince of Songkla University, 2019)
This study was conducted with the following objectives 1) to develop a knowledge set of music culture of the Moken in Surin Archipelago National Park, Pang-nga and to create awareness of the need to preserve it among the Moken youth, and 2) to propose participative plans for network partnership to revitalize, preserve, and sustainably build Moken music as culture capital.The study combined ethnomusicological approaches, including ethnographic fieldwork and in-depth interviews with 5 key informants along with related literature and active research methods between researcher (s), the Moken community, volunteers, and network partnerships focussing on crisis music culture revitalization. The results were: 1) the knowledge set was developed of the music of the Moken for the purposes of revitalization including a knowledge set of Moken music culture and a knowledge set of Kating instruments, involving nine emerging young Moken musicians, 2) Guidelines and measures for fostering participation which include searching for representatives from the community and network partnership, determining the goals and roles of participants, feedback and post-study reflection, and disseminating the results among other Sea Gypsy groups. Suggestions on how to revitalize music culture include an emphasis placed on youth participation as they are vital to the maintenance of the tradition. The mechanism of participation can be further developed to sustainably build the music-culture capital of the Moken in terms of both policy and praxis.